UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KENAKALAN SISWA DI MADRASAH TSANAWIYAH BABUL FUTUH PANDAAN - Dea Lulu Firdausi; Muhammad Hanif; Fita Mustafida (VICRATINA, 2021)
Student delinquency is a problem that still often occurs among teenagers. The following are the efforts of Islamic religious education teachers in overcoming student delinquency at Madrasah Tsanwiyah Babul Futuh Pandaan. In this case the researchers used data collection procedures using the methods of observation, interviews, documentation. From the results of this study, the efforts made by Islamic religious education teachers are to provide advice on a regular basis during and outside learning hours and by making a personal approach to the students concerned and the teacher conducting home visits to students who commit misbehavior.